Tourism as socio-economic phenomenon - Razumei, Yana; Yanenko, Larisa (My University, 2016)
Tourism is a collection of activities, services and industries which deliver a travel experience comprising transportation, accommodation, eating and drinking establishments, retail shops, entertainment businesses and the hospitality services provided for individuals or groups traveling away from home.
Keywords: socio-economic development; world trade; international tourism; світова торгівля; міжнародний туризм; соціально-економічний розвиток; социально-экономическое развитие; мировая торговля; международный туризм; кафедра іноземних мов професійного спрямування